International news flow online global views with local perspectives - Segev, Elad (New York Peter Lang, 2016)
The book explores the theory of news flow around the world, and analyses many of its dimensions such as the global standing of the United States, the Middle Eastern conflicts as seen around the world, and, the effect of financial news. In doing so, the book unveils new patterns, meanings and implications of international news on our perception of the world.
International news flow theory. International news flow: from theory to practice -- International news flow online -- The economic newsworthiness of countries -- Similarities and differences in practice. International news is American -- Global and regional trends in news prominence -- Many local views -- A local outlook of a global conflict -- International news influence. Short-term effect: agenda setting and the news-memory nexus -- Long-term effect: news, global views, and soft power -- International news flow: summary and conclusion -- Caveats and confluction.
Includes bibliographical references (pages 173-186) and index.
Keywords: Journalism -- International cooperation; Online journalism; Mass media and international relations